Speculative film and moving images by or about Black women and girls watch it! - Jeffrey-Legette, Karima K. 1972- (Lexington Books, 2023)
"This book examines twentieth and twenty-first century speculative fiction films that represent women and girls of African descent. Jeffrey offers insights about positive developments while calling attention to questionable trends in recent movie-making"--